Implementasi Program Asistensi Mengajar Berbasis Analisis Statistika dalam Meningkatkan Pembelajaran Matematika Kelas IX di SMP Negeri 23 Medan - Raja Van Den Bosch Sihotang; M. Fariz Fadillah Mardianto (CV. KAMPUS AKADEMIK PUBLISING, 2026)
The Teaching Assistance Program is part of the implementation of the Merdeka Belajar Kampus Merdeka (MBKM) policy, which provides opportunities for students to be directly involved in the learning process at educational units. This study aims to describe the implementation of teaching assistance in Grade IX Mathematics and to analyze the improvement in student learning outcomes using descriptive and inferential statistical approaches. The activities were carried out over 27 effective days at SMP Negeri 23 Medan, with research subjects being students from classes 9A, 9B, 9C, 9D, and 9E. The research method used was descriptive quantitative, with analysis of mean, median, variance, and standard deviation on pretest and posttest scores, followed by a Paired Sample T-Test to determine the significance of differences in learning outcomes. The results showed an increase in the average student score from 42.80 (pretest) to 52.42 (posttest), with a difference of 9.62 points. The statistical test results showed a significance value of 0.000 (p < 0.05), indicating a significant difference between pretest and posttest scores. In addition, the descriptive analysis results showed that classes 9B and 9C had the best performance both before and after learning, while class 9E showed high variation in ability. Overall, the results of the study indicate that the instruction implemented during the teaching assistance activities had a significant effect on improving student learning outcomes. This program not only enhances the quality of learning but also provides an objective overview of students' academic conditions and supports data-driven decision-making in learning strategies.